The Evolution of Religious Influence on Policy: A Review of Historical and Contemporary Studies - Sule, Babayo (FISIP UIN Sunan Gunung Djati Bandung, 2023)
Research Problem: This review aims to explore the dynamic relationship between religion and policymaking, tracing its historical roots and examining its contemporary manifestations. It seeks to understand how religious beliefs, institutions, and ideologies have influenced public policy throughout history and continue to shape governance and societal norms. Research Purposes: The primary purpose of this review is to provide a comprehensive overview of the intricate interplay between religion and policy. It aims to synthesize historical and contemporary studies through a rigorous analytical framework to shed light on the ongoing dialogue between faith and governance in the modern world. Research Methods: Methodologically, this review employs a systematic research method to explore the relationship between religion and policymaking. It utilizes a rigorous analytical framework to synthesize historical and contemporary studies, drawing upon a robust research methodology to enhance understanding of this complex relationship. Results and Discussion: The review delves into the evolving ways in which religious beliefs, institutions, and ideologies have impacted public policy throughout history. It discusses their enduring influence in shaping governance and societal norms, offering insights into the ongoing dialogue between faith and governance in the modern world. Research Implications and Contributions: This review provides valuable insights into the relationship between religion and policymaking, offering a comprehensive overview of its historical roots and contemporary manifestations. By synthesizing historical and contemporary studies, it enhances understanding of the complex interplay between religion and policy, contributing to ongoing dialogue and research in this field.